Representation of Post-Islamism in Hip Hop Music Song Ebith Beat A Collaboration - Kurnain, Genya Anuceni Kurnain (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
Hip-hop music serves as a distinctive platform for expressing identity, struggle, and social reform at the convergence of art, religion, and culture. In Indonesia, hip-hop has fostered forms that confront urban challenges while also incorporating spirituality and contemporary religious beliefs. It aims to elucidate how hip-hop music may articulate the ideology and values of Islamic teachings, while also analyzing the depiction of post-Islamism in the collaborative hip-hop track Ebith Beat A. The research methodology employs Charles Sanders Peirce's semiotic analysis. The study's results indicate that the lyrics of the hip-hop song by Ebith Beat A. Collaboration is rooted in Islamic doctrine, with its foundational principles derived from the Qur'an and sunnah (hadith). All of these elements constitute teachings found throughout Islam. The music ideology serves as a negotiation tool employed by Ebith to communicate Islamic teachings through hip-hop music, which stems from the street music subculture. This signifies the portrayal of Post-Islamism in hip-hop music in partnership with Ebith Beat A